Exploring sustainable processes in construction projects: emerging technologies and opportunities - Lee, Win Nie (2025)
Sustainability and innovation are increasingly shaping the future of the construction industry, with emerging technologies offering new opportunities to enhance environmental, economic, and social performance. This study explores the role of emerging technologies in promoting sustainability in construction projects by identifying key advancements and assessing their practical impacts. Adopting a pragmatic paradigm with a quantitative approach, the study uses a literature review to deductively identify relevant technologies and sustainability potentials, forming the basis for a structured questionnaire. An online survey was conducted among 120 experienced construction professionals, including clients, contractors, and consultants across Malaysia to gather perceptions of the relevancy and effectiveness of smart technologies in sustainability management. The data collected is analysed using descriptive and inferential statistics to derive meaningful insights. Key findings highlight major drivers such as regulatory and market influences, economic and competitive factors, technological advancements, environmental considerations, and strategic motivations. Exploratory factor analysis revealed four underlying factors influencing technology adoption such as policy, innovation and resource-based drivers; environmental and efficiency commitments; market and stakeholder influence; and human awareness and capacity building, offering empirical evidence on industry readiness. The study addresses the gap between technological advancement and sustainability implementation by drawing on industry expertise and identifying key influencing factors. Its novelty lies in presenting a data-driven view of how smart technologies can be strategically integrated to improve sustainability outcomes in construction project management. By aligning industry perceptions with innovation trends, this study offers valuable insights for practitioners and policymakers, supporting a shift toward a more resilient and eco-friendly built environment.